2006
DOI: 10.1590/s1679-62252006000200013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the proximity from an industrial plant on fish assemblages in the rio Paraíba do Sul, southeastern Brazil

Abstract: This work aims to analyze changes in the fish assemblages along a longitudinal reaches of the rio Paraíba do Sul, one of the most used Brazilian aquatic systems, to assess the river "health" and to identify eventual recovery trends. Standardized monthly samplings were carried out at six sites, from October 1997 to September 1999, using casting, sieves, seine and gill nets. Three zones were searched: upstream (Z I), downstream (Z III) and nearby the source of pollution (Z II). Three univariate distribution meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
(58 reference statements)
4
22
0
3
Order By: Relevance
“…Similar distribution patterns for these two species were also found by Araújo et al (2001), with P. reticulata being the most abundant fish species at Z2, while P. caudimaculatus, ranked as the third most abundant species at Z3. The use of deteriorated areas by opportunistic fish species has been reported by several workers (Hughes and Gammon, 1987;Soto-Galera et al, 1998;Harris and Silveira, 1999;Pinto et al, 2006b;Pinto and Araújo, 2007). They have reported that the limitation of natural resources decreased specialist species which are replaced by opportunistic ones, since the latter can use the available resources and cope with the harsh environmental conditions of deteriorated areas.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Similar distribution patterns for these two species were also found by Araújo et al (2001), with P. reticulata being the most abundant fish species at Z2, while P. caudimaculatus, ranked as the third most abundant species at Z3. The use of deteriorated areas by opportunistic fish species has been reported by several workers (Hughes and Gammon, 1987;Soto-Galera et al, 1998;Harris and Silveira, 1999;Pinto et al, 2006b;Pinto and Araújo, 2007). They have reported that the limitation of natural resources decreased specialist species which are replaced by opportunistic ones, since the latter can use the available resources and cope with the harsh environmental conditions of deteriorated areas.…”
Section: Resultsmentioning
confidence: 95%
“…An amount of 160 m 3 /s is pumped from the study area for hydroelectric power and water supply purposes, increasing water quality concerns. Effects of habitat and water deterioration have been described by Pfeiffer et al, 1986;Carvalho and Torres, 2002;Pinto et al, 2006b, who reported large numbers of textile, chemical and food industries, and the presence of the major siderurgic industrial plant at Volta Redonda as the main source of alteration of the system. Additionally, pesticides and herbicides form agricultural activities contribute to add diffuse pollution over the extent of the river, with negative effects on the water quality (Radambrasil, 1983).…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Some have treated morphological description and comparison of the sexes (Gusmão & Pavanelli, 1996). Others have suggested that some species can be used to assess habitat integrity (Bozzetti & Schulz, 2004;Cunico et al, 2006;Ferreira & Casatti, 2006;Pinto et al, 2006;Vieira & Shibatta, 2007), mainly Poecilia reticulata and Phalloceros caudimaculatus.…”
Section: Introductionmentioning
confidence: 99%